Crime scene processing and investigation workbook - Ramirez, Christine R.; Parish-Fisher, Casie L. (Boca Raton, FL : CRC Press, 2019)
Crime Scene Processing and Investigation Workbook, Second Edition is the only workbook which directly supports and cross-references methodology and terminology presented in Ross Gardner and Donna Krouskup's perennial best-seller Practical Crime Scene Processing and Investigations, Third Edition. The workbook serves as supporting material offering hands-on activities to supplement theories and methodologies within the text as well as updated activities to support the new material presented in the Third Edition. As the number of forensic academic programs within the United States continue to grow--and the textbook continues to be a go-to standard in the field--the workbook remains an invaluable reference for academics, forensic training providers, and law enforcement training programs. The detailed Instructor's Manual (IM) lends itself not only to experts who have utilized these procedures before but also to the novice and student who may be introduced to these topics in a classroom setting for the first time. The workbook conducts over 30 activities with detailed instructions, concept overviews, and reflective post-lab questions. Crime Scene Processing and Investigation Workbook, Second Edition, continues to stand as the best workbook on the market, addressing foundational principles in a hands-on manner while directly correlating to the concepts addressed in the Gardner and Krouskup textbook.
OCLC-licensed vendor bibliographic record.
Keywords: Crime scene searches; Criminal investigation; Evidence, Criminal; LAW / Forensic Science; SCIENCE / Chemistry / General